Tensile strength and elasticity of 2 ethyl hexyl acrylate-methylmetha acrylate-acrylonitrile (2 EHA-MMA-AN) Copolymer film - Gogulamurali, N.; Ramaswamy, D. (1987)
The tensile strength and elasticity of copolymer 2 ethyl hexyl acrylate-methylmetha acrylate-acrylonitrile (2-EHA-MMA-AN)- based soft resin was studied using Inston tensile testing machine. It has been found to exhibit plastic flow at room temperature, high extensibility, low tensile strength and more work to fracture. The distribution of micro and macro voids, fibril formation and other properties that affect the tensile strength and elasticity of this polymer 2 EHA-derived resin were also investigated.
Includes bibliographical references (page 100)
Keywords: Physics; Copolymer films -- Mechanical properties